Efficient two-photon luminescence for cellular imaging using biocompatible nitrogen-doped graphene quantum dots conjugated with polymers. Issue 1 (6th December 2017) - Wu, Ping-Ching; Wang, Jiu-Yao; Wang, Wen-Lung; Chang, Chia-Yuan; Huang, Chia-Hung; Yang, Kun-Lin; Chang, Jui-Cheng; Hsu, Chih-Li Lilian; Chen, Shih-Yao; Chou, Ting-Mao; Kuo, Wen-Shuo
Abstract : N-doped GQDs conjugated with polymers demonstrate impressive two-photon properties and stability, and can be used as a contrast agent in deep tissue bioimaging. Abstract : Nitrogen-doped graphene quantum dot (N-GQD) nanomaterials conjugated with polyethylenimine (PEI)-polystyrene sulfonate (PSS)-anti-epidermal growth factor receptor (AbEGFR ) antibody (N-GQD-PEI-PSS-AbEGFR ) demonstrated impressive two-photon properties and stability, signifying that they can serve as an effective two-photon contrast agent in two-photon bioimaging. Furthermore, they provided high intensity, brightness, and signal-to-noise ratios at an ultra-low two-photon excitation (TPE) power level in an observation extending to a deep, three-dimensional depth.